ISLAMIC ETHICS AS THE NORMATIVE FOUNDATION OF EDUCATIONAL PERSONNEL BEHAVIOR - Anggia Rahma Aulia; Julia Agustina (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2026)
The decline in morality, professionalism, and responsibility among some educational personnel has become a challenge in educational management oriented toward character building and humanitarian values. Islamic ethics is considered to play an important role as a normative foundation that directs the behavior of educational personnel in accordance with moral principles and religious values. This article aims to analyze Islamic ethics as a normative basis for the behavior of educational personnel in carrying out their professional duties and responsibilities within educational institutions. This study employs a library research method with a qualitative descriptive approach through the analysis of scientific journals, books, and other relevant literature related to Islamic ethics and educational personnel. The findings reveal that Islamic ethics provides normative guidelines in the form of honesty, trustworthiness, responsibility, discipline, justice, and exemplary conduct as the foundation for shaping professional behavior among educational personnel. The implementation of Islamic ethics in educational settings contributes to the establishment of a professional, harmonious, and integrity-based work culture. Therefore, Islamic ethics can serve as a strong normative foundation in shaping professional, moral, and responsible educational personnel to support the achievement of educational goals